2007
DOI: 10.2320/matertrans.mrp2007198
|View full text |Cite
|
Sign up to set email alerts
|

FeSiBP Bulk Metallic Glasses with Unusual Combination of High Magnetization and High Glass-Forming Ability

Abstract: Among many kinds of bulk metallic glasses (BMGs), Fe-based BMGs with good magnetic properties, high strength and low materials cost should have great potential for wide variety of applications. However, the glass-forming metal elements such as Al, Ga, Nb, Mo, Y and so forth in the Fe-based BMGs significantly decrease saturation magnetization (J s ) which is a essential property as soft magnetic materials and also increase the material cost.The coexistence of high Fe content and high glass-forming ability (GFA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 21 publications
2
51
0
Order By: Relevance
“…2) Excellent soft magnetic properties, such as a low coercivity (³1 A/m), can be obtained by adding metallic and/or metalloid elements (Nb, 3,4) Al, 5) Zr 6) or P 7,8) ) to the FeSiB based materials.…”
Section: Introductionmentioning
confidence: 99%
“…2) Excellent soft magnetic properties, such as a low coercivity (³1 A/m), can be obtained by adding metallic and/or metalloid elements (Nb, 3,4) Al, 5) Zr 6) or P 7,8) ) to the FeSiB based materials.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, based on Fe 76 Si 9:6 B 9:6 P 4:8 BGA 16,17) with high GFA leading to the glassy rods with diameters up to 2.5 mm, the effect of Cr addition on the GFA, magnetic and corrosion properties was discussed. It was found that the addition of small amounts of Cr slightly decreases the magnetic properties, but is very effective in improving corrosion resistance and enlarging the GFA for this Fe-based BGA.…”
Section: Introductionmentioning
confidence: 99%
“…In general, it is well known that the contents of metalloid elements, such as P, C, Si, and B, play a significant role in the formation of metallic glasses in the Fe-based amorphous alloys [10][11][12][13]. In particular, due to atomic interaction and large atomic size differences between B and transition metals, the suitable ratios of B to transition metals, such as Fe, Co, and Ni, lead to the enhancement of its GFA and thermal stability of amorphous alloys.…”
Section: Introductionmentioning
confidence: 99%